1995
DOI: 10.1002/rrr.3450100207
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hydropower peaking on epilithon and invertebrate community trophic structure

Abstract: Hydropower generation induces rapid and frequent fluctuations of hydrodynamic parameters in rivers downstream of hydroelectric impoundments. On the Fontauliere river (Ardeche basin, France , water releases come from the Loire basin and the flow varies from 1.3 to 20m3/s for one reach and from 0.1 to 20m /s for another reach. A reference site upstream was chosen to compare the communities with two downstream impacted sites. These two sites enabled two different base flow situations to be studied simultaneously … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 44 publications
1
32
0
1
Order By: Relevance
“…Hydropeaking is a variant of hydropower production, characterised by introducing rapid and frequent changes in discharge through a hydropower plant. The term 'hydro-peaking' is, however, broad and vaguely defined in the literature, and other terms are also found describing the same phenomenon, such as intermittent hydropower generation (Moog 1993), hydropower peaking (Valentin et al 1995), rapid flow decreases (Bradford 1997), sudden flow variations (Liebig et al 1999), fluctuating flow (Vehanen et al 2000), rapid changes in flow (Saltveit et al 2001), pulse power generation (Scruton et al 2003) and peaking flows (Berland et al 2004). Hydro-peaking has been used to describe both the operational pattern of hydropower plants (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Hydropeaking is a variant of hydropower production, characterised by introducing rapid and frequent changes in discharge through a hydropower plant. The term 'hydro-peaking' is, however, broad and vaguely defined in the literature, and other terms are also found describing the same phenomenon, such as intermittent hydropower generation (Moog 1993), hydropower peaking (Valentin et al 1995), rapid flow decreases (Bradford 1997), sudden flow variations (Liebig et al 1999), fluctuating flow (Vehanen et al 2000), rapid changes in flow (Saltveit et al 2001), pulse power generation (Scruton et al 2003) and peaking flows (Berland et al 2004). Hydro-peaking has been used to describe both the operational pattern of hydropower plants (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Valentin et al (1995) found less diverse and more specialized macroinvertebrate communities in reaches affected by frequent flow fluctuations on the Fontauliere River, France.…”
Section: Long-term Effects Of Dewateringmentioning
confidence: 85%
“…The impact of hydrological regime was mainly studied on periphyton (Biggs and Close, 1989;Acs and Kiss, 1993;Valentin et al, 1995). Nevertheless phytoplankton represents a very sensitive indicator of various environmental changes (Maberly et al, 1994).…”
Section: Introductionmentioning
confidence: 99%